Program Logic Foundations: Putting the Logic Back into Program Logic - Hawkins, Andrew J. (Journal of MultiDisciplinary Evaluation, 2020)
Background: Program logic is one of the most used tools by the public policy evaluator. There is, however, little explanation in the evaluation literature about the logical foundations of program logic or discussion of how it may be determined if a program is logical. This paper was born on a long journey that started with program logic and ended with the logic of evaluation. Consistent throughout was the idea that the discipline of program evaluation is a pragmatic one, concerned with applied social science and effective action in complex, adaptive systems. It gradually became the central claim of this paper that evidence-based policy requires sound reasoning more urgently than further development and testing of scientific theory. This was difficult to reconcile with the observation that much evaluation was conducted within a scientific paradigm, concerned with the development and testing of various types of theory. Purpose: This paper demonstrates the benefits of considering the core essence of a program to be a proposition about the value of a course of action. This contrasts with a research-based paradigm in which programs are considered to be a type of theory, and in which experimental and theory-driven evaluations are conducted. Experimental approaches focus on internal validity of knowledge claims about programs and on discovering stable cause and effect relationships—or, colloquially, ‘what works?’. Theory-driven approaches tend to focus on external validity and in the case of the realist approach, the search for transfactual causal mechanisms—extending the ‘what works’ mantra to include ‘for whom and in what circumstances’. On both approaches, evaluation aspires to be a scientific pursuit for obtaining knowledge of general laws of phenomena, or in the case of realists, replicable context-mechanism-outcome configurations. This paper presents and seeks to justify an approach rooted in logic, and that supports anyone to engage in a reasonable and democratic deliberation about the value of a course of action. It is consistent with systems thinking, complexity and the associated limits to certainty for determining the value of a proposed, or actual, course of action in the social world. It suggests that evaluation should learn from the past and have an eye toward the future, but that it would be most beneficial if concerned with evaluating in the present, in addressing the question ‘is this a good idea here and now? Setting: Not applicable. Intervention: Not applicable Research design: Not applicable. Findings: In seeking foundations of program logic, this paper exposes roots that extend far deeper than the post-enlightenment, positivist and post-positivist social science search for stable cause and effect relationships. These roots lie in the 4th century BCE with Aristotle’s ‘enthymeme’. The exploration leads to conclusions about the need for a greater focus on logic and reasoning in the design and evaluation of programs and interventions for the public good. Science and research are shown to play a crucial role in providing reasons or warrants to support a claim about the value of a course of action; however, one subordinate to the alpha-discipline of logical evaluation and decision making that must consider what is feasible given the context, capability and capacity available, not to mention values and ethics. Program Design Logic (PDL) is presented as an accessible and incremental innovation that may be used to determine if a program makes sense ‘on paper’ in the design stage as well as ‘in reality’ during delivery. It is based on a configurationalist theory of causality and the concepts of ‘necessary’ and ‘sufficient’ conditions. It is intended to guide deliberation and decision making across the life cycle of any intervention intended for the public good.